2009
DOI: 10.2527/jas.2008-1718
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of very long-chain fatty acids as complementary or alternative natural fecal markers to n-alkanes for estimating diet composition of goats feeding on mixed diets1

Abstract: This study aimed to assess the use of very long-chain fatty acids (VLCFA) as an alternative or a complement to n-alkane markers for estimation of diet composition of goats fed 7 different diets, composed of different proportions of herbaceous (Lolium perenne and Trifolium repens) and heathland woody species (Erica umbellata, Erica cinerea, Calluna vulgaris, Erica arborea, and Ulex gallii), in a metabolism study. Diet composition was estimated from VLCFA (i.e., C(22) to C(34)) and alkane (i.e., C(25) to C(33)) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
63
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(81 citation statements)
references
References 25 publications
16
63
2
Order By: Relevance
“…For cattle, a positive association between CCL and LCOH FR was found. A similar trend was observed for horses and cattle when using LCFA (Ferreira et al, 2010) and alkanes (Ferreira et al, 2007 and2009a), and also in other ruminant species when studying LCOH (Ali et al, 2004;Dove and Charmley, 2008), LCFA (Ali et al, 2004;Ferreira et al, 2009b and and alkanes (Dove and Mayes, 2005;Ferreira et al, 2005 and2009a;Charmley and Dove, 2007). These data indicated that markers behave differently in the gastro-intestinal tract of ruminant and nonruminant species, and suggest that the disappearance of those with the shorter carbon-chain in the gut of ruminants occurs to a greater extent than in non-ruminants.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…For cattle, a positive association between CCL and LCOH FR was found. A similar trend was observed for horses and cattle when using LCFA (Ferreira et al, 2010) and alkanes (Ferreira et al, 2007 and2009a), and also in other ruminant species when studying LCOH (Ali et al, 2004;Dove and Charmley, 2008), LCFA (Ali et al, 2004;Ferreira et al, 2009b and and alkanes (Dove and Mayes, 2005;Ferreira et al, 2005 and2009a;Charmley and Dove, 2007). These data indicated that markers behave differently in the gastro-intestinal tract of ruminant and nonruminant species, and suggest that the disappearance of those with the shorter carbon-chain in the gut of ruminants occurs to a greater extent than in non-ruminants.…”
Section: Discussionsupporting
confidence: 73%
“…It should be pointed out that the superiority of LCOH markers found in this study, may be situation dependent and the selection of one type of marker should also be based on the marker concentrations in the possible diet components and its capability of discriminating between them (Ferreira et al, 2012), discarding types of marker with very low concentrations in plant species within the diets. It is usually suggested that markers with very low concentrations have greater measurement errors in their analytical determination (Dove and Mayes, 2005) and their utilization may result in less accurate estimates of diet composition (Charmley and Dove, 2007;Ferreira et al, 2009b).…”
Section: Diet Composition Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of diet composition estimates as a whole was assessed using the Kulczynski similarity index (KSI), which calculates the overlap between observed and estimated diet composition using different markers and different sets of faecal recovery correction, as follows (Kerbs, 1989;Ferreira et al, 2009a):…”
Section: Calculationsmentioning
confidence: 99%
“…To date, these studies have been conducted by feeding known mixtures of two to five components to livestock, based on alkanes alone (Charmley and Dove, 2007;Lin et al, 2007;Ferreira et al, 2009b), and different combinations of alkanes and alcohols (Dove and Charmley, 2008) or alkanes and acids (Ferreira et al, 2009a). Moreover, the studies for evaluating the potential use of alkanes, alcohols and acids as diet composition markers were based on even more simple diets with three components (Ali et al, 2005;Lin et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%